Information overload: a concept analysis - Belabbes, Mohamed Amine; Ruthven, Ian; Moshfeghi, Yashar; Rasmussen Pennington, Diane (Journal of documentation, 2023)
PurposeWith the shift to an information-based society and to the de-centralisation of information, information overload has attracted a growing interest in the computer and information science research communities. However, there is no clear understanding of the meaning of the term, and while there have been many proposed definitions, there is no consensus. The goal of this work was to define the concept of “information overload”. In order to do so, a concept analysis using Rodgers' approach was performed.Design/methodology/approachA concept analysis using Rodgers' approach based on a corpus of documents published between 2010 and September 2020 was conducted. One surrogate for “information overload”, which is “cognitive overload” was identified. The corpus of documents consisted of 151 documents for information overload and ten for cognitive overload. All documents were from the fields of computer science and information science, and were retrieved from three databases: Association for Computing Machinery (ACM) Digital Library, SCOPUS and Library and Information Science Abstracts (LISA).FindingsThe themes identified from the authors’ concept analysis allowed us to extract the triggers, manifestations and consequences of information overload. They found triggers related to information characteristics, information need, the working environment, the cognitive abilities of individuals and the information environment. In terms of manifestations, they found that information overload manifests itself both emotionally and cognitively. The consequences of information overload were both internal and external. These findings allowed them to provide a definition of information overload.Originality/valueThrough the authors’ concept analysis, they were able to clarify the components of information overload and provide a definition of the concept.